Portrait of Student's Learning Interest in Integrated Science Learning During the COVID-19 Pandemic - Ahmad Walid; Naintyn Novitasari; Mukti Hari Wiji Aziiz; Suharyati Suharyati (Online Learning In Educational Research (OLER), 2021)
Education determines the success of a country. Every educational action requires results and learning interest. This research aims to determine the profile of students' learning interest in Integrated Science learning during the COVID-19 pandemic. The research method used is the descriptive-quantitative. The research population are the students of SMP Negeri 02 Tebat Karai of Kepahiang. The research sample consisted of 20 students determined by the purposive sampling technique. The instrument used is a close-ended questionnaire using the Likert scale. The data is reprocessed in a descriptive percentage. The results show that students average learning interest in Integrated Science learning during the COVID-19 pandemic is high. Although the results are relatively high, students learning interest needs to be improved further. If students have a high learning interest, they will have a curiosity. Students with a high learning interest can have achievements, even though the learning process is carried out online during the current pandemic.